2015
DOI: 10.1038/ijo.2015.175
|View full text |Cite
|
Sign up to set email alerts
|

Intensive lifestyle treatment for non-alcoholic fatty liver disease in children with severe obesity: inpatient versus ambulatory treatment

Abstract: A 6-month intensive inpatient and ambulatory lifestyle treatment in children with severe obesity reverses NAFLD in a minority of patients. This study suggests that inpatient compared with ambulatory intensive treatment does not importantly increase treatment success. Further efforts to optimize and individualize lifestyle interventions and additional treatments options are needed particular for children with severe obesity resistant to conventional lifestyle interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 38 publications
(39 reference statements)
1
39
0
1
Order By: Relevance
“…There was significantly greater rate of achieving the outcome in relation to the intensity of the intervention (inpatient 43%, ambulatory 33%, usual care 22%). A similar trend was seen for normalization of ALT (inpatient 41%, ambulatory 33%, usual care 6%) [24]. …”
Section: Combination Of Nutrition and Exercisesupporting
confidence: 71%
“…There was significantly greater rate of achieving the outcome in relation to the intensity of the intervention (inpatient 43%, ambulatory 33%, usual care 22%). A similar trend was seen for normalization of ALT (inpatient 41%, ambulatory 33%, usual care 6%) [24]. …”
Section: Combination Of Nutrition and Exercisesupporting
confidence: 71%
“…The AASLD practice guidelines indicate that weight loss of least 3–5% appears necessary for improving steatosis, but a greater loss (up to 10%) may be needed to alleviate necroinflammation23. A recent study showed that intensive inpatient and ambulatory treatments are more effective than usual care24. According to Vilar-Gomez et al 25,.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant therapy did not improve liver histology, but children in both groups who had already reduced their weight through designated lifestyle changes showed significant improvement in steatosis, inflammation, ballooning, and the NAS. In one study consisting of 51 children with severe obesity (BMI z‐score >3.5) and NAFLD, intensive lifestyle modification (either in an inpatient or ambulatory setting) offered sustained biochemical benefits in comparison to usual care …”
Section: Aspects Of Nafld Specific To Children and Adolescentsmentioning
confidence: 99%